2018
DOI: 10.1002/hrm.21942
|View full text |Cite
|
Sign up to set email alerts
|

Employee stock ownership and financial performance in European countries: The moderating effects of uncertainty avoidance and social trust

Abstract: This study investigates how the effect of employee stock ownership on financial performance may hinge on the diverse cultural and societal contexts of European countries. Based on agency and national culture theories, we hypothesize that the positive relationship between employee stock ownership and return on assets (ROA) is stronger in those nations with lower uncertainty avoidance and higher social trust. Using a multisource, time‐lagged, large‐scale dataset of 1,741 firms from 21 countries in Europe, our mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 135 publications
(196 reference statements)
1
13
0
1
Order By: Relevance
“…However, prior literature such as Bova et al (2015b) and Chen et al (2020) has concluded that employee ownership is large enough to drive employee incentives and affect corporate policies. The preponderance of prior empirical research finds positive association between non-executive employee ownership and both firm performance and innovation, supporting the view that employee shareholding aligns the interests of employees with those of other shareholders (Chang et al 2015;Kim and Patel 2017;Kang and Kim 2019). Bova et al (2015a) report that firms tend to disclose more information when employees have larger stakes in the firm.…”
Section: Introductionmentioning
confidence: 73%
“…However, prior literature such as Bova et al (2015b) and Chen et al (2020) has concluded that employee ownership is large enough to drive employee incentives and affect corporate policies. The preponderance of prior empirical research finds positive association between non-executive employee ownership and both firm performance and innovation, supporting the view that employee shareholding aligns the interests of employees with those of other shareholders (Chang et al 2015;Kim and Patel 2017;Kang and Kim 2019). Bova et al (2015a) report that firms tend to disclose more information when employees have larger stakes in the firm.…”
Section: Introductionmentioning
confidence: 73%
“…Given the prevalence of these stock purchase plans, it is somewhat surprising that academic research seeking to answer questions about the impact of such plans on employees and employers has been slow to emerge. However, a recent special issue of Human Resource Management is an indication of increasing scholarly interest in the topic (Basterretxea, Heras‐Saizarbitoria, & Lertxundi, ; Kang & Kim, ; Kim & Han, ). Despite these recent advancements, very little is known about the determinants of an employee's decision to participate in a stock purchase plan and the inherent risk borne by employees.…”
Section: Introductionmentioning
confidence: 99%
“…Akademiniame lauke ryški tyrimų tematika, kurioje nustatomas ryšys tarp darbuotojų nuosavybės ir įmonės veiklos veiksmingumo (Kim, Patel, 2017). Dalis atliktų empirinių tyrimų atskleidė ryšius tarp įmonės veiklos rezultatų (darbuotojų produktyvumas, finansiniai rezultatai, personalo valdymo stabilumas) ir darbuotojų finansinio dalyvavimo (Kang, Kim, 2019;Kurtulus, Kruse, 2018;Richter, Schrader, 2017;Whitfield ir kt., 2017).…”
unclassified